Synthesis of oligonucleotides on cellulose by a phosphotriester method. - Crea, R (1980)
The synthesis of oligothymidilic acids, (dT)m (where m = 4, 7, 10, 13, 16, 19, 22, and 25), was carried out using a solid phase approach in combination with the modified phosphotriester methodology developed in solution. Cellulose was used as the solid support after its functionalization with a specially featured dinucleoside diphosphate, 5'-0-p-chlorophenylphospho-2'(3')-0-acetyluridilyl-[2'(3')-3']-5'-0-dimethoxytritylthymidine p-chlorophenylester. The fully protected trideoxynucleoside triphosphate containing only thymidine was repeatedly used to elongate the oligonucleotide chain in the 3'-5' direction. Individual coupling yields ranged from 45% to 75%. The total time needed to prepare (dT)25 was four days. Similarly, the tridecanucleotide d(AGAAGGTACTTTT) was synthesized in good yield. The results show that this approach can be used for a fast and economic way to synthesize oligodeoxynucleotides.